2020
DOI: 10.1016/j.jesf.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of two high-intensity circuit training protocols: Does sequence matter?

Abstract: Background/objectiveThe integration of high-intensity interval training (HIIT) and circuit weight training (CWT) is seamless and practical for meeting recommended exercise guidelines. The purpose of this study was to determine the ideal combination of HIIT and CWT to elicit desired acute cardiorespiratory and metabolic responses in variables such as energy expenditure (EE), oxygen consumption (VO2), heart rate (HR), blood lactate (BLa−), excess post-exercise oxygen consumption (EPOC), rating of perceived exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…min -1 , which is similar to values observed in a Crossfit study 25 and corresponding to high intensity, as recommended by the ACSM -exercises performed above 6 METS are considered as intense 26 . Similarly, both the heart rate data of the present study (86.87%) and previous reports [3][4][5] , as well as in studies with boot camp, naval rope, jumps, and circuit training, all agree that it attains values above those proposed (85% of maximum predicted HR) by ACSM for high-intensity exercise (85% of predicted maximum HR) [28][29][30] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…min -1 , which is similar to values observed in a Crossfit study 25 and corresponding to high intensity, as recommended by the ACSM -exercises performed above 6 METS are considered as intense 26 . Similarly, both the heart rate data of the present study (86.87%) and previous reports [3][4][5] , as well as in studies with boot camp, naval rope, jumps, and circuit training, all agree that it attains values above those proposed (85% of maximum predicted HR) by ACSM for high-intensity exercise (85% of predicted maximum HR) [28][29][30] .…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, few studies have investigated the energy expenditure in exercise sessions that used only bodyweight 17,28 . The total energy expenditure of 251.05 ± 27.26 kcal or 12.63 ± 2.24 kcal.min -1 found in this study was similar to those in other high-intensity modalities 17,23,[27][28][29][30][31] . Using the burpee exercise, Ratamess, Rosemberg, Klei et al 17 showed that 10s all-out repetitions, with a 2-minutes interval, resulted in an expenditure of approximately 9.6 ± 1.kcal.min-1.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, HIIT can also affect metabolic processes by increasing anabolic processes and helping in the metabolism of high-speed energy-supplying substrates in balance with energy expenditure and replenishment. This can help individuals in conditions of working ability, especially in more precise execution and speed of activities or work [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis showed that combination training has a greater effect on cognitive function in older adults than aerobic exercise training alone 22 . Circuit training is defined as the performance of 6–12 exercises in sequential order with little to no break between them 23 . A novel type of circuit training program involves a combination of the two aforementioned training modalities, namely, a resistance training set followed immediately by an aerobic exercise interval (a simultaneous aerobic-resistance training method).…”
Section: Introductionmentioning
confidence: 99%